De-internationalization: A business model perspective - Jesper Chrautwald Sort; Romeo V. Turcan (Journal of Business Models (JOBM), 2019)
Through business model theoretical lenses, we explore the impact of de-internationalization on firms and their industries and challenges in re-configuring their business models and re-thinking their value propositions in response to de-internationalization. This is a conceptual paper. We put forward a multilevel framework to advance our understanding of this intersection.
Keywords: 650; Business model; de-internationalization; value renewal; re-internationalization